2018
DOI: 10.1016/j.gaitpost.2018.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of joint kinematic calculations based on direct kinematic and inverse kinematic models in obese children

Abstract: Reliability values showed clinically acceptable error-margins and were comparable between all models. Therefore, our results support the careful use of IK models in overweight or obese populations, e.g. for musculoskeletal modelling studies. The inconsistent kinematic output can mainly be explained by different model conventions and anatomical segment coordinate frame definitions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 30 publications
4
8
0
Order By: Relevance
“…In the PiG, the pelvis anatomical coordinate system is oriented such that the anteroposterior axis lies in a plane defined by the pelvis markers (sacrum and two anterior iliac spines), whereas the axis for the mGen is oriented parallel to the horizontal. This led to a RMSD difference of about 10-15 • , which was shown to reduce by adjustment of the anatomical and joint reference frames [10,11]. Similarly, in this study, an RMSD of 18 ± 1.5 • in pelvic tilt between the PiG and mGen approaches was found.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…In the PiG, the pelvis anatomical coordinate system is oriented such that the anteroposterior axis lies in a plane defined by the pelvis markers (sacrum and two anterior iliac spines), whereas the axis for the mGen is oriented parallel to the horizontal. This led to a RMSD difference of about 10-15 • , which was shown to reduce by adjustment of the anatomical and joint reference frames [10,11]. Similarly, in this study, an RMSD of 18 ± 1.5 • in pelvic tilt between the PiG and mGen approaches was found.…”
Section: Discussionsupporting
confidence: 69%
“…This is most likely to be attributed to the differences in degrees of freedom observed between the two models. In fact, Horsak et al [11] showed in a group of obese children that using three instead of one degree of freedom at the knee joint in mGen reduced the RMSD between mGen and PiG estimates of hip rotation. From their results, it could also be observed that the R 2 improved with a 3-DoF mGen knee.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We believe instead that the greater repeatability of the markerless kinematics compared to those from previous studies is more likely due to the markerless tracking method itself. We acknowledge that greater differences may be seen if the knee and hip joints were additionally allowed 6DOF; however, other studies have shown similar reliability between IK and DK techniques and there is currently no implemented option for 6DOF knee and hip joints in Theia3D (Mentiplay and Clark, 2018;Horsak et al, 2018).…”
Section: Discussionmentioning
confidence: 95%